Is leg length a biomarker of early life conditions? Evidence from a historically short population - Sohn, Kitae (John Wiley & Sons, Inc., 2015)
© 2015 Wiley Periodicals, Inc.Objectives: While one group (Positive Group) has argued that leg length is a more accurate biomarker of early life conditions than height, another group (Negative Group) has challenged this argument. Analyzing Indonesian data, we attempt to reconcile these contrasting arguments. Methods: The sample consists of 4,193 men and 4,684 women, aged 40-70. We regress leg length, trunk length, and height each on education (a proxy for early life conditions), age, and ethnicity. We also adjust for hip size and shrinkage. Results: The relationship is statistically significant for leg length, which is generally consistent with the assertion of the Positive Group. However, the relationship is smaller than that for height, which is generally consistent with that of the Negative Group. Specifically, an additional year of schooling is associated with a 0.080 cm longer leg length for men and 0.078 cm for women. The corresponding figures for height are 0.260 cm and 0.201 cm. This remains true when the magnitude of the relationship is compared with the mean length. Conclusions: Small sample sizes appear to drive the Negative Group's finding that leg length is not statistically significantly related to early life conditions. However, the magnitude of the relationship confirms the Negative Group's argument that leg length is not a more accurate biomarker of early life conditions than height.